Production of bioactive peptides during yogurt fermentation, their extraction and functional characterization - Cakmakoglu, Selma Kayacan; Dere, Sevda; Bekiroglu, Hatice; Bozkurt, Fatih; Karasu, Salih; Dertli, Enes; Turker, Mustafa; Sagdic, Osman (ELSEVIER, 2024)
This study aimed to evaluate the antioxidant, antibacterial, antidiabetic and angiotensin-converting enzyme (ACE)-inhibitory effects of different fractions of bioactive peptides produced as a result of milk fermentation with yogurt starters and probiotics. In addition to yogurt starters, milk was fermented separately and together with Lacticaseibacillus rhamnosus GG and L. paracasei, then passed through 5 and 10 kDa (kilodalton) filters. A significant difference was observed in the fermentation time between the samples. The antioxidant, antibacterial, antidiabetic and ACE-inhibitory activities of the bioactive peptides were significantly affected by the probiotic strains and the molecular weight of the peptide (p < 0.05). <= 5 kDa fractions of Lactobacillus delbrueckii subsp. bulgaricus + Streptococcus thermophilus + L. rhamnosus GG + L. paracasei had the highest antioxidant activity. The addition of L. rhamnosus GG and L. paracasei to yogurt starter significantly increased alpha-amylase activity, alpha glucosidase activity and ACE inhibitor activity. All samples showed antibacterial activity to Escherichia coli, Staphylococcus aureus, and Salmonella Typhimurium microorganisms and the molecular weight of peptides and sample types were significantly exhibited in antibacterial activity (p < 0.05). Cytotoxic activity showed that bioactive peptides had cytotoxic effect against Caco-2 adenocarcinoma cell and the presence of probiotics increased the cytotoxic effect. The results of the study suggest that the use of L. rhamnosus GG and L. paracasei, together with yogurt starters, could improve the bioactive properties of peptides formed in dairy products.
Keywords: Yogurt starters; L. rhamnosus GG; L. paracasei; Fermentation; Peptides; Ultrafiltration; I-CONVERTING-ENZYME; ALPHA-GLUCOSIDASE; LACTOBACILLUS-RHAMNOSUS; ANTIMICROBIAL ACTIVITY; INHIBITORY-ACTIVITIES; BOVINE-MILK; ANTIOXIDANT; CAMEL; IDENTIFICATION; ANTIBACTERIAL; Food Science & Technology